The voyage of the Serliana motif, a journey to understand the transmission of architectural values through space and time - Cimadomo, Guido (My University, 2019)
Following the idea of a drastic reduction of linguistic tools in the early Renaissance we have to assume a recovery of the Serliana motif only in the 16th century, after its practical disappearance for several centuries. Palladio's Quattro Libri, together with Serlio's treatise definitely impulsed the use of the Serliana, after the recovering of this element made during the16th century. The outcomes of this research, through the analysis of treatises and other documents, offer an attempt to understand the context that made possible the reborn and great diffusion of the Serliana in Italy and soon in the rest of Europe. The outcomes outline a possible alternative way in which the Serliana reached Italy, landing in Venice before other Renaissance centers, giving enhanced value to the idea of a contamination of architecture and culture through Europe.
Keywords: Arquitectura - Historia; Serliana; Cultural transmission; History of Architecture